DEVELOPMENT OF ANNUAL LANDSAT 8 COMPOSITE OVER CENTRAL KALIMANTAN, INDONESIA USING AUTOMATIC ALGORITHM TO MINIMIZE CLOUD - Kustiyo (BRIN, 2016)
Since January 2013, Landsat 8 data can be freely accessed from LAPAN, making it possible to use the all available Landsat 8 data toÂ produce the cloud-free Landsat 8 composite images. This study used Landsat 8 archive images in 2015,Â Operational Land Imager (OLI) sensor in 30 meter resolution, geometric correction level of L1T. The eight data in L1T of 118-062, southern part of Central Kalimantanwere used to produce a cloud-free composite image. Radiometric correction using Top of Atmosphere (TOA) and Bidirectional Reflectance Distribution Function (BRDF) algorithm to produce reflectance images have been applied, and then the most cloud-free pixels were selected in composite result. Six composite methods base on greens, open area and haze indices were compared, and the best one was selectedÂ using visual analysis. The analysis shows that the composite algorithm using Max (Max (NIR, SWIR1)/Green) produces the best image composite.